Effect of FeO Content on Melting Characteristics and Structure of Nickel Slag - Shen, Yingying; Ma, Yutian; Yang, Peng; Lu, Bingang; Dou, Yinli; Tian, Jianke; Guo, Wenbo; Zhang, Zhongqing (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
A great deal of nickel slag is produced in the process of nickel smelting, which contains a lot of Fe in the form of FeO in the molten slag. The effect of FeO content on the melting characteristics and structure of nickel slag is study via thermodynamic calculation and experiments, with the nickel slag of water quenching furnace as raw material which is simplified to CaO-SiO2-FeO-MgO slag system. The results are shown as follows: With the increasing of FeO content, the precipitated primary phase changes from melilite to olivine. The liquidus temperature, softening temperature, hemispheric temperature, flow temperature, viscosity and critical viscosity temperature of slag system tends to decrease gradually, but the solid phase temperature tends to decrease first and then increase. The centre of [SiO4]4- tetrahedron symmetric stretching vibration band in the slag system moves to the low wave number region. The mole fraction of O0 in the slag decreases continuously, the mole fraction of O- and O2- increases. The complex silicon-oxygen tetrahedron structure gradually disintegrates and the structural unit tends to be simple.